Delay in seeking treatment and associated factors among women with pelvic organ prolapse in Bale Zone, Southeast Ethiopia: a hospital-based cross-sectional study - Neway Ejigu; Kenbon Seyoum; Degefa Gomora; Chala Kene; Sheleme Mengistu; Girma Geta; Mujib Abdella; Alemitu Ayele; Yaregal Admasu; Ayinamaw Embiale; Telila Mesfin; Derese Eshetu; et al. (SAGE Publishing, 2024)
Background: Pelvic organ prolapse (POP) is a major reproductive health problem that severely affects women's quality of life in several ways. Women who suffer from POP silently wait to heal from their problem without seeking care until the disease progressively worsens. Objective: The aim of this study was to assess factors associated with delay in seeking treatment among women with POP at public hospitals in Bale Zone, Southeast Ethiopia. Design: Facility-based cross-sectional study. Methods: A total of 344 study participants were enrolled at public hospitals in Bale Zone, Southeast Ethiopia, from 20 February to 20 May 2023. A consecutive sampling method was used to select the respondents. Data were collected using a pretested interviewer-administered structured questionnaire. Both bivariable and multivariable logistic regressions were used to identify the predictors of the outcome variable. Both the crude odds ratio (COR) and adjusted odds ratio (AOR) along with a 95% confidence interval (CI) were used to estimate the strength of the association between predictors and the response variable. Results: This study revealed that out of 333 participants, 76.9% (95% CI: 72.1, 81.4) were delayed in the treatment of POP. The median time of delay for POP treatments was 36 [interquartile range (IQR): 24-96] months. Being a rural resident [adjusted odds ratio (AOR) = 2.02, 95% CI: 1.23, 4.00], autonomous decision-making (AOR = 5.46, 95% CI: 2.30, 10.85), lack of support (AOR = 3.94, 95% CI: 1.64, 9.48), an embarrassment to see male health care providers (AOR = 2.04, 95% CI: 1.09, 3.81), and a lack of knowledge about successful POP treatment (AOR = 2.29, 95% CI: 1.27, 4.14) were significantly associated with delay of treatment for POP. Conclusion: A large number of women with POP did not seek health care in this study: Being in rural, autonomous decision-making, a lack of support, an embarrassment to see male health care providers, and a lack of knowledge on successful treatment were associated with treatment delay. Educating women and the community to make them aware that it is a treatable condition and encourage women's independence in decision-making on health care services in the family will improve their quality of life.